Kebijakan Hukum terhadap Tindak Pidana Penangkapan Ikan Secara Ilegal di Perairan Indonesia - Eko Budi S (Universitas Batanghari Jambi, 2018)
Legal policy against fisheries offenders is basically directed at the accountability of fisheries offenders (illegal fishing). The impact of illegal fishing causes a deterioration in the national economy and increasing social problems in the Indonesian fisheries community. The Republic of Indonesia Law Number. 45 of 2009 concerning amendments to the Republic of Indonesia Law Number. 31 of 2004 concerning Fisheries has regulated criminal acts (offenses) in the field of fisheries which are divided into 2 categories, namely the category of violations and crimes. The effectiveness of law enforcement is still lacking because there are still a number of obstacles, including the substance, structural, supporting infrastructure, the community and the culture of the community itself. The Indonesian government has made efforts to minimize these obstacles through several strategies in order to eradicate the practice of illegal fishing in Indonesian waters